CRITERION MODEL OF AN EARTH SCIENCE TEACHER PREPARATION PROGRAM. - Mayer, Victor J. (Science Education, 1967)
The article discusses the doctoral dissertation, entitled "A study of existing pre-service earth science teacher preparation programs," submitted in partial fulfillment of requirements for PhD degree at the University of Colorado in 1966. The dissertation evaluates the various guidelines and recommendations for an earth science teacher preparation program. The recommended academic program includes a one year course work in each of the basic sciences and in mathematics and preparation in the history and philosophy of science. Recommendations are also made on instructional methods, professional science education requirements, staffing, equipment and facilities.